2022
DOI: 10.1177/01614681221093282
|View full text |Cite
|
Sign up to set email alerts
|

The (In)Visibility of Race in School Discipline Across Urban, Suburban, and Exurban Contexts

Abstract: Background/Context: Racial disparities in school discipline represent a long-standing injustice in U.S. schools. Students of color, particularly Black students, are systematically subjected to harsher school disciplinary actions compared with their peers. A growing body of evidence demonstrates the severity of the problem and the negative consequences of harsh punishment, particularly given that students who are disciplined are more likely to be forced into the complex nexus of education and incarceration. Foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Few studies, for instance, examine the role of professionals' beliefs and perceptions of students of color in disproportionality (Cruz et al, 2021). Even fewer studies have targeted the perspectives of stakeholders in schools at distinctive locations such as suburban settings (see Ahram et al, 2011;Skiba et al, 2006;Tefera et al, 2022). Skiba et al (2006) documented how teachers explained the causes of disproportionality and found that ''cultural gaps and misunderstandings [between teachers and students of color] may intensify behavioral challenges'' [which was a significant issue for teachers] (p. 1424) (see also Ahram et al, 2011).…”
Section: Tefera Et Almentioning
confidence: 99%
“…Few studies, for instance, examine the role of professionals' beliefs and perceptions of students of color in disproportionality (Cruz et al, 2021). Even fewer studies have targeted the perspectives of stakeholders in schools at distinctive locations such as suburban settings (see Ahram et al, 2011;Skiba et al, 2006;Tefera et al, 2022). Skiba et al (2006) documented how teachers explained the causes of disproportionality and found that ''cultural gaps and misunderstandings [between teachers and students of color] may intensify behavioral challenges'' [which was a significant issue for teachers] (p. 1424) (see also Ahram et al, 2011).…”
Section: Tefera Et Almentioning
confidence: 99%
“…Race-evasive discipline policies and practices do not consider the role of race and racism, while race-conscious school discipline policies or practices do. Although all schools in our study adopted written policies and practices to address discipline disparities (Siegel-Hawley et al, 2019; Tefera et al, 2022), we found they were largely race-evasive and did little to disrupt racial disparities. Leaders and educators pointed to practices they believed directly addressed disparities, including interventions such as Positive Behavioral Interventions and Supports (PBIS), professional development, and data collection.…”
Section: Race-evasive Interventions and Practicesmentioning
confidence: 74%
“…Leaders and educators pointed to practices they believed directly addressed disparities, including interventions such as Positive Behavioral Interventions and Supports (PBIS), professional development, and data collection. These practices, however, were largely symbolic and race-evasive (Bowker & Star, 1999;Tefera et al, 2022), which contributed to districts' ongoing issues with discipline disparities.…”
Section: Race-evasive Interventions and Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies find that educators often use colorblind, neoliberal logic to explain racial disparities in school discipline, believing Black students’ character, ability, or inherent deficiencies are the root cause of inequity—reinforcing the idea that Black students are not mistreated but deserving of harsher treatment (Gregory & Mosely, 2004; Sondel et al, 2019; Tefera et al, 2022; Welsh, 2023a). This shift in blame may result in policies and practices that locate the crisis of educational inequities within Black students and families themselves, evading responsibility for deep structural changes and instead developing solutions that wrongfully attempt to force assimilation and adaptation among Black students through punishment and exclusion.…”
Section: Antiblackness In School Disciplinementioning
confidence: 99%